QOL-56. QUALITY OF LIFE IN SURVIVORS OF CHILDHOOD BRAIN TUMORS. Issue 2 (22nd June 2018) - Channell, Jessica; Raybin, Jennifer; Foreman, Nicholas; Hutaff-Lee, Christa
Abstract: BACKGROUND: As survival rates for children with pediatric central nervous tumors (CNS) improve, long term quality of life is increasingly salient. METHODS: Between June 2003 and November 2017, patients with intracranial tumors, at least 5 years off therapy, and their parents were approached during follow up visits. After completing informed consent, children and parents completed a quality of life scale (Health Status Index). RESULTS: 64 participants (M=17.95 years, SD=3.99) and 65 parents completed the questionnaires. Average age at diagnosis was 9 years (range: 2 months-20 years). Average number of years off therapy was 8.5 years (range: 5-19 years). Forty-two (72%) subjects received radiation. Participants endorsed difficulties with recalling information (63%) and learning/remembering schoolwork (46%). A smaller percentage (32%) reported cognitive problems involving thinking and solving everyday problems. Parent rating revealed similar concerns regarding their child's ability to recall information (36%) and cognitive difficulties (29%). Both parents and children rated concerns regarding gross (12%) and fine motor concerns (10% and 18%, respectively), social interactions (13% and 44%, respectively), and cosmetic problems (15%). Interestingly, parent and child ratings significantly differed (p = <.01) in three areas: pain management (parents = 24%, child = 9%), level of pain (parents = 24%, child = 9%), and hearing problems (parents= 6 %, child= 10%). CONCLUSIONS: Similar to the literature, cognition and memory were the highest reported concerns by parents and children followed by motor and social-related issues; however, other concerns differed between the two groups. Further work is needed comparing survivor's concerns versus their caretakers.